STRATEGI PENGEMBANGAN DESA WISATA PULUTAN MENUJU DESA WISATA MANDIRI DI KABUPATEN GUNUNGKIDUL - Indriyaningsih Septeri, Dyah; Samsuharjo (Mimbar Administrasi Mandiri, 2025)
The purpose of this study was to analyze how the development strategy of Pulutan Tourism Village towards an independent tourism village in Gunungkidul Regency. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The Pulutan Village Valley object is still the main attraction and a leading tourist attraction in Pulutan Village. The many local potentials owned by the tourist village have not been able to attract tourists to stay for a long time in Pulutan Village. Through SWOT analysis, various components of Pulutan Tourism Village can be seen, which can be developed into an independent or sustainable tourist village. The components of the tourist village include the tourist attractions offered, accessibility that is quite supportive of tourists, and adequate amenities. Starting from the opening of the tourist attraction until December 2024, the Pulutan Village Valley has been recorded as having attracted 519,781 tourists. Responding to this positive trend, in 2024 the Pulutan Village Government together with the Pulutan Maju Mandiri Village BUM will optimize the focus of development of both road infrastructure and Lembah Desa facilities in order to increase the comfort and attractiveness of tourists. The final stage, through the formulation of the SWOT matrix analysis, can be carried out the development of Pulutan Tourism Village towards an independent tourism village, which is expected to have an impact on increasing the economic resilience of the local community. Efforts that can be made are to adopt the preparation of a sustainable tourism village development strategy using PESTEL Analysis to realize the development of Pulutan Tourism Village towards an independent tourism village in Gunungkidul Regency.